The Role of the Claustrum in Parkinson’s Disease and Vascular Parkinsonism: A Matter of Network? - Marialuisa Zedde; Rocco Quatrale; Gianni Cossu; Massimo Del Sette; Rosario Pascarella (Life)
Background: The mechanisms underlying extrapyramidal disorders and their anatomical substrate have been extensively investigated. Recently, the role of the claustrum in Parkinson’s disease and other neurodegenerative conditions has been better detailed. The main aim of this review was to summarize the supporting evidence for the role of the claustrum in degenerative and vascular parkinsonism. Methods: The anatomy, biology, vascular supply, and connections of the claustrum in humans were identified and described, providing the substrate for the vascular involvement of the claustrum in large- and small-vessel disease. The vascular supply of the claustrum includes up to three different sources from a single artery, the middle cerebral artery, and it is known as territory with an intermediate hemodynamic risk. The connections of the claustrum make it a sensory integrator and a relevant point in several networks, from consciousness to movement planning. Conclusions: The claustrum is still an incompletely explained structure. However, recent description of its multiple connections indicate that it is involved in several diseases, including Parkinson’s disease. The evidence underlying its potential role in vascular parkinsonism is still scarce, but it might be a field warranting future investigations.